Forms of Misleading Information in Sharia Fintech Marketing and Their Implications For Consumer Protection: A Maqashid Sharia Analysis - Azza Nayla; 'Azizatuz Zulfa Hidayatun Mahfudhoh Zulfa (Al-Muamalat: Journal of Islamic Economics Law, 2026)
ENGLISH The use of Instagram as a promotional tool for sharia fintech has the potential to lead to misleading information practices, particularly in the form of profit overclaim, omission of risk disclosure, and the use of ambiguous “sharia-compliant” labels without adequate explanation, such as claims of profits without properly explaining the risks. The purpose of this study is to analyze the forms and patterns of misleading information practices in the marketing of sharia fintech on Instagram and their implications for consumer protection according to applicable law and maqashid sharia principles, particularly the protection of wealth (hifdz al-mal) and intellect (hifdz al-‘aql). This study applies a normative legal method with an approach to legislation and conceptual thinking, complemented by a qualitative content analysis of selected Instagram promotional materials to identify concrete misleading patterns. The findings show that the marketing methods used still have weaknesses in meeting the principles of transparency and honesty, as reflected in recurring patterns such as selective information disclosure, emphasis on guaranteed returns, and insufficient explanation of potential losses, which have the potential to harm consumers. Therefore, there needs to be improvements in supervision, increasing consumer knowledge, and implementing marketing ethics in line with sharia values to achieve fairer consumer protection INDONESIA Penggunaan Instagram sebagai alat promosi untuk fintech syariah berpotensi memicu praktik informasi yang menyesatkan (misleading information), terutama dalam bentuk klaim keuntungan yang berlebihan (profit overclaim), tidak dicantumkannya pengungkapan risiko (omission of risk disclosure), dan penggunaan label "patuh syariah" yang ambigu tanpa penjelasan yang memadai, seperti klaim keuntungan tanpa menjelaskan risikonya dengan benar. Tujuan dari penelitian ini adalah untuk menganalisis bentuk dan pola praktik informasi yang menyesatkan dalam pemasaran fintech syariah di Instagram serta implikasinya terhadap perlindungan konsumen menurut hukum yang berlaku dan prinsip-prinsip maqashid syariah, khususnya perlindungan harta (hifdz al-mal) dan akal (hifdz al-‘aql). Penelitian ini menerapkan metode hukum normatif dengan pendekatan perundang-undangan dan pendekatan konseptual, yang dilengkapi dengan analisis isi kualitatif terhadap materi promosi Instagram terpilih untuk mengidentifikasi pola penyesatan yang konkret. Temuan penelitian menunjukkan bahwa metode pemasaran yang digunakan masih memiliki kelemahan dalam memenuhi prinsip transparansi dan kejujuran, yang tercermin dari pola berulang seperti pengungkapan informasi secara selektif, penekanan pada jaminan imbal hasil, dan penjelasan yang tidak memadai mengenai potensi kerugian, sehingga berpotensi merugikan konsumen. Oleh karena itu, perlu adanya peningkatan pengawasan, peningkatan pengetahuan konsumen, serta penerapan etika pemasaran yang sejalan dengan nilai-nilai syariah demi mewujudkan perlindungan konsumen yang lebih adil